The global role of bioassessment in policy delivery and decision-making for inland waters - Kelly, M. G.; Free, G.; Simaika, John; Warner, S.; Bruder, A.; Correa-Bedoya, A.; de Oliveira Roque, F.; Eriksen, T. E.; Lento, J.; Macadam, C. R.; Meissner, K.; Moretti, M. S.; et al. (Elsevier, 2025)
Bioassessment is necessary to guide the management of freshwater ecosystems and promote sustainable water use. However, many countries either do not have nationally-approved bioassessment systems, or their bioassessment results are not used in water policy decision-making. Despite the importance and urgency of the topic, a global overview of bioassessment and its use in decision-making is missing. In this study, we analyzed survey responses from 341 bioassessment practitioners from 109 countries to examine the role bioassessment plays in freshwater governance. Two thirds of respondents reported that bioassessment was used in their country, with the strength of the link to legislation increasing with per capita Gross Domestic Product (GDP). Bioassessment data generally fulfilled several roles, including following trends over time and developing catchment plans, both significantly linked to increased per capita GDP. Strong relationships with stressors were cited as a strength of bioassessment over other forms of evidence gathering, whilst costs and shortage of trained staff were the most common weaknesses. Governance is key, being the main factor explaining why some countries don’t have bioassessment and enabling its enaction through legislation in others. Initiatives therefore need to focus on creating an “enabling environment” as well as financial and technical aspects. We found synergies between having international agreements and using bioassessment for communication when delivering nationally important roles for bioassessment. By identifying key drivers for using bioassessment in decision making, our study provides recommendations to inform future research, policy and practice.